Synthesis and Application of ZnO/SiO2 Composite for Methylene Blue Degradation by Photocatalyst Process and Its Kinetics - Sunardi; Sumardiyono; Muhamad Ariyanto Adi Saputro; Soebiyanto (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Methylene blue is considered a persistent organic pollutant due to the presence of a benzene group that resists degradation, making it difficult to break down. One source of SiO2 is volcanic ash from volcanic eruptions, which accounts for more than 50% of the total mixture of compounds. The abundant SiO2 in volcanic ash can be utilised and converted into silica gel by forming potassium silicate through the chemical interaction between the SiO2 present in volcanic ash and potassium hydroxide. The ZnO/SiO2 composite has been used as an adsorbent to degrade methylene blue artificial dye. This study aims to determine the composition that gives maximum results in MB dye degradation. ZnO/SiO2 composite with volume ratio of 1:1, 1:2, 1:3. In this study, the dye degradation under sunlight and UV light exposure was investigated and the effect of various factors such as mass, time, concentration and pH to achieve the highest possible degradation of MB dye was also studied. The results showed that the most effective reduction in MB dye concentration occurred when using a ZnO/SiO2 composite with a 1:3 ratio, using 100 mg of adsorbent, subjecting it to UV irradiation for 60 minutes, and working with a dye concentration of 10 g/l at a relatively neutral pH of 6. The dye degradation efficiency obtained under these conditions was 97.63%